2016
DOI: 10.1007/s00394-016-1311-0
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran protein hydrolysates reduce arterial stiffening, vascular remodeling and oxidative stress in rats fed a high-carbohydrate and high-fat diet

Abstract: RBPH mitigate the deleterious effects of HCHF through potential mechanisms involving enhanced NO bioavailability, anti-ACE, anti-inflammatory and antioxidant properties. RBPH could be used as dietary supplements to minimize oxidative stress and vascular alterations triggered by MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…The anti-hypertensive activity of G6RB was also confirmed in Sprague-Dawley (SD rats fed a high-carbohydrate and high-fat (HCHF) diet and in L-NAME-administered SD rats. Upregulation of NOS expression was also observed in both studies [ 49 , 50 ]. The authors discussed that small peptides aid in the anti-hypertensive effects of G6RB, but they remain unidentified [ 50 ].…”
Section: Anti-hypertensive Effects Of Protease-digested Rice Bransupporting
confidence: 55%
“…The anti-hypertensive activity of G6RB was also confirmed in Sprague-Dawley (SD rats fed a high-carbohydrate and high-fat (HCHF) diet and in L-NAME-administered SD rats. Upregulation of NOS expression was also observed in both studies [ 49 , 50 ]. The authors discussed that small peptides aid in the anti-hypertensive effects of G6RB, but they remain unidentified [ 50 ].…”
Section: Anti-hypertensive Effects Of Protease-digested Rice Bransupporting
confidence: 55%
“…Cell morphology changes as a result of H 2 O 2 damage being ameliorated and cell apoptosis was significantly lowered through the attenuation of cleaved caspase-3 levels as observed post RB peptide treatment [39]. A similar effect was demonstrated in vivo after RB protein hydrolysate supplementation in atherosclerosis-prone rats fed with a high-carbohydrate and high-fat diet [40]. Significant improvements to levels of hyperglycemia, insulin resistance, dyslipidemia, hypertension, aortic pulse wave velocity, aortic wall hypertrophy and vascular remodelling was observed [40].…”
Section: Rice Bran Derived Bioactive Compounds and Biomarkers Of Cmentioning
confidence: 90%
“…Our previous studies revealed that peptides‐derived from Thai jasmine rice bran also have strong in vitro antioxidant and ACE inhibitory activities (Timachai, ; Kaewjumpol & Thawornchinsombut, ; Kaewjumpol et al , ). Results from in vivo studies of peptides from cold‐pressed defatted Thai jasmine rice bran exhibited beneficial effects on antihypertensive properties by inhibiting ACE and vasodilatory and antioxidant activities (Boonla et al , ), antihyperglycemic effects by improving insulin sensitivity and precluding diabetic nephropathy (Boonloh et al , ; Boonloh et al , ), as well as the improvement of metabolic changes and hemodynamic status, and a reduction in aortic stiffening, vascular dysfunction, inflammation and oxidative stress (Senaphan et al , ). In our preliminary experiment, the fractionation of the Thai jasmine RBPH using ultrafiltration membranes obtained from fractions of 10–50 kDa and <10 kDa were able to concentrate protein from 37.8 (10–50 kDa) to 47.6 (<10 kDa) g/100 g RBPH powder.…”
Section: Introductionmentioning
confidence: 99%